Reconstruction of Empty Sockets with Sahaf?s Orbital Implant - Imran Akram Sahaf, Zahid Kamal, M Rizwan Ullah, Girdhari Lal, Abdula Hye (Pakistan Journal of Ophthalmology, 2010)
Purpose: To measure the out come of Sahaf’s orbital implant in empty sockets with little or no recognizable extraocular muscles. Material and Methods: A Quasi Interventional study was done in the department of ophthalmology of Lahore General Hospital Lahore from August 2006 to April 2009. Thirty eyes of 30 patients were included in this study. Sahaf Orbital implant is a polymethyl methacrylate orbital implant. It has pear shaped base, truncated edge. It is inert, cost effective, has no cutting edges and easily available in Pakistan. Three sizes are available to restore volume and enhance support of the prosthesis after implantation. After explaining the procedure a special written consent for surgery and anesthesia was taken by patient. The surgical technique included opening the conjuvtiva, tenon and fibrous tissue with a horizontal incision made with Blade No 15. Deepening of the incision to the orbital apex with a blunt tipped pair of scissors. Widening of the wound to the orbital wall by opening the scissors. Result: Sahaf orbital implant inserted deep to the apex of the orbit with its flat base resting on the orbital floor. Tenon and conjunctiva sutured over implant in two layers separately. Wrapping of Donar sclera or autogenous fascia lata used in most cases. The patients followed at 4, 8, 12 weeks and 6 months after the operation. The patients received a prosthetic eye after 6 weeks by the ocularist. Conclusion: All patients had excellent cosmetic results, without any serious side effects. Sahaf orbital Implant has a special design to adjust to different sized orbits. It gives excellent fill to the orbit by using various sizes. It is economical and cost effective. It is readily available to the ophthalmologists in Pakistan. It also gives better adjustment initially to conformer and later to the prosthesis. The technique of implantation is very easy. Any general ophthalmologist can do it very easily.